(untitled) (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2018)
Today there are many schools – the school started foreign language lesson in good things, including the Arabic one. Even students in the pre-school category-began to introduced with languages-foreign languages. Parents or teachers may be glad when his son started to be proficient in the use of foreign languages. But whether the teaching of foreign languages at pre-school age children is in compliance with the development of his cognitive. The purpose of this study is to describe the process of activity teaching Arabic in kindergarten and explain how the view of the theory of the development of kognitf Jean Piaget against the teaching process. On the principle of cognitive developmental theory of Jean Piaget said that children at pre-school age already have a symbolic and intuitive function is active. Both of these functions that can help students in doing a second language acquisition. Material presented is adapted to the development of cognitive learners. Teaching methods undertaken by teachers is a method which can enhance the active role of the learners in the lesson. However, teachers should always do their teaching in the process of creation, this is to cultivate the interest of learners in learning Arabic.